The Law Role of Business Competition to Develop the Global and Indonesian Economy - Nadir, Nadir (International Journal of Law and Society, 2025)
This study examines the role of law in regulating business competition to develop the economy is needed. The purpose of this research is to find out and reveal the role of law in developing the economy. This research method uses normative legal research method, it is intended to identify and reveal the role of law in economic development. The results of this study indicate that the role of law in regulating business competition to develop the economy is very much needed so that business competition runs orderly and does not violate the rights of fellow business actors. The role of this law is manifested in government policies required by developing countries far beyond the needs of the developed industrial countries which have been established. The developed countries already have legal mechanisms in place to accommodate changes in their societies. Meanwhile, developing countries are not like that. In fact, the hopes and desires of people in developing countries for the realization of changes that bring about a greater improvement in living standards exceed the expectations needed by people in developed countries. The growth and economic development of the Indonesian state and in the world will be much influenced by fair business competition among business actors, both now and in the future. While, the healthy competition will be determined by legal policies in economic development; legal policies in business competition; politics of law formation and decision-making processes in the formation of business competition law